Rare bird documentation form for Peregrine Falcon at Lake Diamond County Park, 1980 - Newlon, Michael C.et al (1980)
Rare bird documentation form for a Peregrine Falcon at Lake Diamond County Park in Poweshiek County, IA on September 21, 1980. Epson - sheet feed